Rs9939609 Variant of the Fat Mass and Obesity-Associated Gene and Trunk Obesity in Adolescents - Harald Mangge; Wilfried Renner; Gunter Almer; Daniel Weghuber; Reinhard Möller; Renate Horejsi (Journal of Obesity)
A common T/A polymorphism (rs9939609) in the fat mass and obesity associated (FTO) gene was found associated with early-onset and severe obesity in both adults and children. However, recent observations failed to find associations of FTO with obesity. To investigate the genetic background of early obesity, we analysed the single nucleotide polymorphism (SNP) rs9939609 of FTO in 371 styrian adolescents towards degree of obesity, subcutaneous adipose tissue (SAT)-distribution determined by lipometry, early metabolic and preatherosclerotic symptoms. The percentage of AA homozygotes for the rs9939609 SNP of FTO was significantly increased in the obese adolescents. Compared to the TT wildtype, AA homozygotes showed significantly elevated values of SAT thickness at the trunk-located lipometer measure points neck and frontal chest, body weight, body mass index, waist, and hip circumference. No associations were found with carotis communis intima media thickness, systolic, diastolic blood pressure, ultrasensitive C-reactive protein (US-CRP), homocystein, total cholesterol, triglycerides, HDL cholesterol, oxidized LDL, fasted glucose, insulin, HOMA-index, liver transaminases, uric acid, and adipokines like resistin, leptin, and adiponectin. Taken together, to the best of our knowledge we are the first to report that the rs9939609 FTO SNP is associated with trunk weighted obesity as early as in adolescence.